A new double layer super-capacitor made by free-standing activated carbon membranes and highly concentrated potassium acetate solutions. (20th December 2020) - Tribbia, M.; Pianta, N.; Brugnetti, G.; Lorenzi, R.; Ruffo, R.
Abstract: Water in salt solutions are a new class of electrolytes developed with the aim of increasing the electrochemical stability of aqueous electrolytes without decreasing the transport properties. Among them, aqueous solutions of potassium acetate (CH3 COOK, AcK) have received little attention, despite its large solubility in water at room temperature (25 mol kg −1 ) and the very low cost. With the idea of developing cost-effective and good performing Electrochemical Double Layer Capacitors (EDLCs), a symmetric device based on a low-cost coal derived carbon (F400) and highly concentrated AcK solutions as electrodes and electrolytes, respectively, was fabricated and optimized. The best results are obtained with the system F400/20 mol kg −1 AcK/F400 able to deliver a gravimetric energy density of 26 Wh kg −1 at an average power of 1.4 kW kg −1 .